1993
DOI: 10.1002/hlca.19930760108
|View full text |Cite
|
Sign up to set email alerts
|

(o‐Hydroxyphenyl)methylphosphonic acids: Synthesis and potentiometric determinations of their pKa Values

Abstract: (o-Hydroxypheny1)methylphosphonic acids are readily obtained from o-(bromomethy1)-or o-(hydroxymethy1)phenols and trialkyl phosphites. Subsequent hydrolysis leads to the corresponding phosphonic acids. For a series of such compounds, the pK, values have been determined by potentiometry. Their dependence on additional substituents in the aromatic ring is discussed in terms of electronic and steric effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 13 publications
0
15
1
Order By: Relevance
“…The comparison of these results with those obtained with 2-hydroxy 5-methyl phenyl 1,3-dimethylphosphonic acid [25] (pK a1 = 1.46, pK a2 = 2.47, pK a3 = 6.51, pK a4 = 8.31, pK a5 = 11.88) indicates that these values are higher (pK a1 excepted) than those given in this paper. This shows that our ligands, with two aromatic moieties, are very powerful acids.…”
Section: Deprotonation Processcontrasting
confidence: 55%
See 1 more Smart Citation
“…The comparison of these results with those obtained with 2-hydroxy 5-methyl phenyl 1,3-dimethylphosphonic acid [25] (pK a1 = 1.46, pK a2 = 2.47, pK a3 = 6.51, pK a4 = 8.31, pK a5 = 11.88) indicates that these values are higher (pK a1 excepted) than those given in this paper. This shows that our ligands, with two aromatic moieties, are very powerful acids.…”
Section: Deprotonation Processcontrasting
confidence: 55%
“…More recently, the study of intramolecular stacking interactions in ternary Cu(II) complexes formed with an heteroaromatic amine and 9-[2-(2-phosphonoethoxy)ethyl]adenine was published [24]. Chafaa et al [25,26] have reported the acidbase properties of a series of (o-hydroxyphenyl) methylenephosphonic acids synthesized by Vogt et al The stability constants of the complexes obtained from these ligands and bivalent transition metals cations [27,28] and a wide variety of lanthanide(III) cations and thorium(IV) were determined [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…This is necessary in order to determine the hydrolysis constants that are to be injected as fixed values for the calculation of the stability constants of the complexes of lanthanides (III) and of thorium (IV) cations with (phenolic) monoand dimethylenephosphonic acids [17,18] synthesised by Böhmer et al [19]. The treatment by Sirko-P [20] and Superquad [21] of the different titration curves corresponding to different lanthanides permitted the interpretation of this increase of H + ions concentration by the following hydrolysis equilibriums:…”
Section: Hydrolysis Of Lanthanides (Iii) and Of Thorium (Iv)mentioning
confidence: 99%
“…All the compounds were synthesized as described by Bö hmer et al [11] Ligand solutions were kept away from light, in order to avoid degradation, and were used, at the latest, 5 days after their preparation. The lanthanide (III) chlorides were commercial products p.a.…”
Section: Reagentsmentioning
confidence: 99%